74 Anticipatory prescribing in palliative care: evaluation of current practice. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Ponnampalampillai, Abiramithevi; Marvin, Ros; Grove, Sarah; Barclay, Stephen; Spathis, Anna
Abstract : Background: National guidelines endorse prescription of medications in anticipation of symptoms in the last days of life. Little is known about current practice in anticipatory prescribing (AP). A service evaluation was undertaken to evaluate AP across one county in the UK. Method: Electronic records were searched of patients known to the Bedfordshire PEPS (Partnership for Excellence in Palliative Support) Co-ordination Centre, who had died during a one-year period and had been prescribed injectable medications for symptom control. Results: Out of 392 eligible patients, the records of 132 were selected at random. 486 injectable medications were prescribed: 77% were in anticipation of symptoms and 23% in response to existing symptoms. Diamorphine and midazolam were most commonly prescribed in anticipation, with 43/88 (49%) and 41/93 (44%) prescriptions leading to drug administration respectively. The corresponding data for glycopyrronium, cyclizine, haloperidol and metoclopramide were 25/78 (32%), 15/67 (22%), 3/11 (27%) and 3/14 (21%). Overall, only 37% of all medications prescribed in anticipation were administered. Recognition of the need for AP came from palliative care nurses (50%), GPs (32%) and District Nurses (14%). Most patients had malignant disease (87%). The median time between prescription and first drug administration was 9 days in patients with cancer (range 0–368), and 61 days in those with non-malignant disease (range 3–298). Conclusion: Most prescribing of injectable medications was in anticipation, rather than in response to, symptoms. About a third of anticipatory prescribing led to drug administration. Although diamorphine and midazolam were both commonly prescribed and administered, antiemetics were less so. Further work is needed to evaluate the cost-effectiveness of AP, particularly in relation to antiemetics, and to investigate the unexpectedly long interval between drug prescription and administration in patients with non-malignant disease.